2021
DOI: 10.1097/md.0000000000024673
|View full text |Cite
|
Sign up to set email alerts
|

The effects of peripheral anterior synechiae on refractive outcomes after cataract surgery in eyes with primary angle-closure disease

Abstract: Objective of the study was to investigate the effects of peripheral anterior synechiae (PAS) on refractive outcomes after cataract surgery in eyes with primary angle-closure disease (PACD). This is a retrospective, cross-sectional study. Seventy eyes of 70 PACD patients who underwent phacoemulsification and intraocular lens implantation. Patients were divided into 2 groups based on the presence of PAS on preoperative gonioscopy. The predictive power of the intraocular lens was calculated by the SRK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Consequently, discrepancies are unsurprising in IOL prediction in eyes with PACD. Additionally, currently available studies conducted among PACD eyes showed divergent accuracies of different formulas [7,9,21,[24][25][26]. All these facts stress the importance of our study.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Consequently, discrepancies are unsurprising in IOL prediction in eyes with PACD. Additionally, currently available studies conducted among PACD eyes showed divergent accuracies of different formulas [7,9,21,[24][25][26]. All these facts stress the importance of our study.…”
Section: Discussionsupporting
confidence: 53%
“…synechial angle closure without/with glaucomatous neuropathy in the PACD spectrum (i.e., PAC, PACG). Though PACS was also mentioned in some studies [9], the fact that it did not strictly follow the ISGEO definition led to our exclusion of the data in case any bias were introduced. Furthermore, given that less than 1% of PACS would progress into PAC/PACG per year as stated by He et al [28] and that only 2.5~3.75% PACS ultimately develop PAC/PACG [29], PACS might be an independent subgroup different from PAC/PACG in view of pathogenesis and prognosis.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Так, например, согласно многочисленным клиническим исследованиям и описаниям случаев и их серий, набухающая масса катаракты может привести к синехиям передней капсулы хрусталика со зрачковым краем радужки, что может блокировать отток внутриглазной жидкости с задней камеры глаза в переднюю [12][13][14]. Из-за подобного нарушения дренажной системы глаза, сдвинутая вперед радужная оболочка с сопутствующими пролиферативными процессами может привести к передним синехиям, в итоге закрывая доступ к трабекулярной формации, откуда происходит основной дренаж жидкости глаза [14,15]. К ряду осложнений можно так же отнести сублюксацию и дислокацию хрусталикового материала, увеиты, кератиты и другие воспалительные патологии [12,[16][17][18][19][20].…”
Section: оптимизация организации оказания офтальмологической помощи б...unclassified
“…In addition to the pupillary block factor, non-pupillary block factors such as plateau iris syndrome, lens-related factors, or retrolental factors may affect the APAC crisis. In most of the eyes, more than one mechanism may be involved in the pathogenesis of angle closure [1].…”
Section: Introductionmentioning
confidence: 99%